Identification and Confirmation of the miR-30 Family as a Potential Central Player in Tobacco-Related Head and Neck Squamous Cell Carcinoma - Zhang, Tingting; Zhu, Xueqin; Sun, Qiang; Qin, Xing; Zhang, Zhen; Feng, Yuanyong; Yan, Ming; Chen, Wantao (Frontiers in Oncology, 2021)
Constituents of tobacco can cause DNA adduct formation and are implicated in the development of head and neck squamous cell carcinoma (HNSCC). However, there are few studies on the mechanism(s) that underlie tobacco-associated HNSCC. Here, we induced tumors in rats using 4-nitroquinoline 1-oxide (4NQO), a useful model that mimics tobacco-related HNSCC, and analyzed the expression profiling of microRNAs and mRNAs. Our results indicated that 57 miRNAs and 474 mRNA/EST transcripts exhibited differential expression profiles between tumor and normal tongue tissues. In tumor tissue, the expression levels of the rno-miR-30 family (rno-miR-30a, -30a*, -30b-5p, -30c, -30d, -30e and -30e*) were only 8% to 37% of their counterparts in the control group. Three members of the rno-miR-30 family (rno-miR-30a*, -30d, and -30e*) were the three highest degrees of miRNAs based on the miRNA-gene networks, and members rno-miR-30 b-5p, -30c, -30d, and -30e were four of the highest degrees of miRNAs uncovered by miRNA-go-network. The maximum-enrichment GOs targeted by the differentially expressed miRNA-30 family include forward locomotion, striated muscle cell development, ADP transport, and the beta-alanine catabolic process. QRT-PCR was performed to validate the low expression of miR-30 family in human HNSCC tissues and cell lines (P<0.05). MTT, colony formation and transwell migration assay indicated that miR-30e-5p or miR-30b-5p inhibited the proliferation and migration in human HNSCC cell lines (P<0.05). Thus, our data clearly showed that decreased expression of the miR-30 family may play a crucial role in carcinogenesis development, especially in metabolic processes and cell movement. Further investigations are needed to understand the role of the miR-30 family regulatory mechanism during the development of HNSCC.